Pengembangan Media Pembelajaran Tanaman Obat Tradisional Menggunakan Metode Multimedia Development Life Cycle - Muhammad Fauzan Yasykur; Neo Mauizan Ali Fitrah; Nanda Ega Wijaya Saputra (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2024)
Maintaining health is a crucial aspect of human life, and one traditional method to boost the immune system is through the use of medicinal plants. The practice of using medicinal plants has been passed down through generations, but in the present era, there is a decline in interest, particularly among the younger generation due to a lack of knowledge about the benefits of medicinal plants. This research aims to develop an interactive learning media introducing traditional medicinal plants, named "Herba Wisdom," as a solution to educate the younger generation on harnessing the benefits of medicinal plants. In an effort to create innovative learning media, this study will implement the Multimedia Development Life Cycle (MDLC) method. MDLC serves as a structured framework in the development of learning media, ensuring quality and consistency throughout the development process. The development will be carried out using Construct 2, a practical, fast, and efficient platform for creating interactive multimedia. The research employs black-box testing to assess program functionality, resulting in a program that operates effectively and provides a high level of user satisfaction.